2019
DOI: 10.1029/2019gc008329
|View full text |Cite
|
Sign up to set email alerts
|

Postmagmatic Tectonic Evolution of the Outer Izu‐Bonin Forearc Revealed by Sediment Basin Structure and Vein Microstructure Analysis: Implications for a 15 Ma Hiatus Between Pacific Plate Subduction Initiation and Forearc Extension

Abstract: International Ocean Discovery Program Expedition 352 recovered sedimentary-volcaniclastic successions and extensional structures (faults and extensional veins) that allow the reconstruction of the Izu-Bonin forearc tectonic evolution using a combination of shipboard core data, seismic reflection images, and calcite vein microstructure analysis. The oldest recorded biostratigraphic ages within fault-bounded sedimentary basins (Late Eocene to Early Oligocene) imply a~15 Ma hiatus between the formation of the ign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 97 publications
(237 reference statements)
3
18
0
Order By: Relevance
“…This implies that the rate of mineral growth approximated the rate of fracture opening (Fisher & Brantley, 1992;Hilgers et al, 2001). Extensional veining at Sites U1439-U1441 fits well into the concept of an extensional forearc regime where normal faults, grabens, and half-grabens (Christeson et al, 2016;Robertson et al, 2018) related to slab rollback and trench retreat are observed Kurz et al, 2019). In accordance with this interpretation, the Izu-Bonin rear arc Site U1438 lacks syntaxial veins as well as large-scale extensional structures (…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…This implies that the rate of mineral growth approximated the rate of fracture opening (Fisher & Brantley, 1992;Hilgers et al, 2001). Extensional veining at Sites U1439-U1441 fits well into the concept of an extensional forearc regime where normal faults, grabens, and half-grabens (Christeson et al, 2016;Robertson et al, 2018) related to slab rollback and trench retreat are observed Kurz et al, 2019). In accordance with this interpretation, the Izu-Bonin rear arc Site U1438 lacks syntaxial veins as well as large-scale extensional structures (…”
Section: Discussionsupporting
confidence: 66%
“…Transitional veins occur predominantly in the Izu-Bonin forearc Sites U1439-U1441, whereas the rear arc Site U1438 exposes a high number of purely antitaxial veins with length-width ratios >100. We therefore suggest that the extensional regime in the Izu-Bonin forearc (Christeson et al, 2016;Kurz et al, 2019) inhibited widespread antitaxial veining. Transitional veins may accordingly reflect antitaxial veining that was preceded, accompanied, or succeeded by extensional fracturing, whose path of propagation was predetermined by zones of weakness such as preexisting (antitaxial) veins.…”
Section: 1029/2019gc008745mentioning
confidence: 81%
See 3 more Smart Citations